Maceração enzimática de película comestível de cajá (Spondias mombin L.) para a extração de carotenóides - Vieira, Janaína Maria Martins (2010)
Brazil is third largest producer in sector of fruit production. Northeast stands out due to flavor and aroma of exotic fruit and its enormous diversity. However, parts of fruit, and perishable, are seasonal, hence need to seek technical and economic alternatives to use of surplus production, allowing for consumption and export throughout the year. The increase in production creates a concern about environmental impacts caused to natural ecosystems. The problems related to solid waste generation, and its effect on health, environment and quality of life has worsened in recent decades due to lack of institutional policies for sector. A strong example of how these fruits is fruit of hog plum tree (Spondias mombin L.), which in Brazil is found mainly in North and Northeast. Other fruits and vegetables contain different antioxidants, whose activities have been well documented in recent years. Presence of phenolic compounds such as flavonoids, phenolic acids, antiocianinas, besides those already known, vitamins C, E and A contribute to the beneficial effects of these foods. Presence of carotenoids in the yellow mombin, and especially in its waste, allowed its use for extracting carotenoids from their pellicle by enzyme maceration. Initially this was done to establish the composition of pellicle and then characterization of enzymatic complexes to be used. For maceration were conducted as preliminary analysis: evaluation of pulp reason: water, amount of enzyme to be added, and determine the best enzyme complex to be used. We also evaluate the need for grinding yellow mombin edible pellicle. In the extraction of carotenoids by enzymatic hydrolysis, there was a fractional factorial design 2 (k-1) with central point, which varied factors as amount of enzyme, maceration temperature and maceration time. It was found that yellow mombin edible pellicle presents physical-chemical richer in terms of protein and lipids that the pulp yellow mombin. Enzyme preparations showed pectinolytic activities, xylan, amylolytic and cellulolytic. Reason pulp: water suitable for soaking pellicle was 1:4, and time crunch was more efficient 30s. Enzyme preparation Pectinex XXL was more efficient in maceration of yellow mombin edible pellicle, probably due to their higher content of pectinoliase. It is possible to extract carotenoids from yellow mombin edible pellicle by enzymatic hydrolysis using aqueous medium. The condition of better recovery of carotenoids used 150μL of enzyme complex, 3h liquors at a temperature of 35° C.